Pajak Bumi dan Bangunan (PBB) - Pasaribu, Khoirunnisa; Syakira, Elyana (Media Hukum Indonesia (MHI), 2025)
Land and Building Tax (PBB) is one type of tax that plays an important role in supporting funding for national and regional development. Since the implementation of fiscal decentralization through Law No. 28 of 2009, the management of PBB for the urban and rural sectors (PBB-P2) has been handed over to local governments, so that PBB has become an important component of Regional Original Income (PAD). This article reviews the definition, legal basis, objectives, collection mechanisms, as well as issues and efforts to improve the PBB system. Despite its strategic role, the implementation of PBB still encounters obstacles in the form of low levels of tax compliance, inaccurate taxable object sales value (NJOP), and weak administrative systems. Innovations such as digitalization of services, data updates, and public education are important solutions in optimizing PBB as a fair and sustainable fiscal tool.